Analysis and research of methods of EFL teaching in the context of intercultural communication in China - Lin, Liyuan (Язык и культура : сборник статей XXXIV Международной научной конференции (15, 16, 17 октября 2024 г.))
From China's reform and opening up to the proposal of the Belt and Road Strategy to the present day, with the increasingly close exchanges with other countries and the deepening of globalization, there has been a growing demand for international talents with intercultural communication competence and the requirements are getting higher and higher. English, as the most widely used language so far, EFL teaching at university plays a crucial role in the cultivation of intercultural communication competence in order to fully utilize its international communication function. Based on this background, combined with China's actual condition and the characteristics of globalization, EFL teaching methods in China in the context of intercultural communication are analyzed with the aim of cultivating compound talents with intercultural communication competence.